Shaping an urban space: the revitalization process of Mouraria in Lisbon - Corte-Real, Madalena Sandmann (2017)
The present thesis addresses revitalization processes, an important strategy for the contemporary city, based on a redefinition of the urban fabric, taking as a case study Mouraria in the so-called historic part of Lisbon, an area which had been considered by different actors, both internally and externally, as requiring an intervention in order to respond to physical decay and social vulnerabilities. The research aimed to analyze how a territory is shaped, by following local interventions and capture the changes that happen in a context of transition. In view of the global transformations with local consequences, urban policies tend to prioritize a concerted action at the local level via interventions that reflect the growing trend of combining economic growth and social justice. In this respect, by working in partnership, this model aims to enhance the competitiveness of cities and the socioeconomic development of territories by supporting entrepreneurial initiatives, improving public space, and boosting the housing market. These approaches focus on territories as evaluative goods, where new possibilities are to be explored by aesthetically elevating the landscape and recreating a local symbolic identity that is promoted for leisure and consumption. In this sense, the presence of organizations that work in the social sector, and increasingly from the cultural industry, which is considered by local government as a key element in the redevelopment of local meanings, is to be encouraged. At the same time, startup financing to trigger social entrepreneurship, a penetration of the middle class, which is attracted by locally-created opportunities, the media's role as well as online networks in disseminating trends in terms of urban realities, are important aspects in redefining a territory. In the reproduction of social action, new forms of appropriation, relocation and delimitation can be identified but also perpetuation.